SAT0125 Association of Rituximab Levels to Clinical Response and B Cell Recovery in Rheumatoid Arthritis Patients. (23rd January 2014) - Sarmiento Guevara, M.; Diaz Torne, C.; Ortiz, M. A.; Torres, N.; Nagore, D.; Diaz Lopez, C.; Geli, C.; de Llobet, J. M.; Juarez, C.; Vidal, S.
Abstract : Background: Rituximab effects in rheumatoid arthritis patients have been extensively described in the literature. However, kinetics of rituximab levels in serum and their association with the clinical and immunological changes in these patients remain unknown. Methods: Thirty five patients were treated with three courses of rituximab (one course: 1000 mg administered intravenously on days 1 and 15). Levels of rituximab in the serum were determined by ELISA (Promonitor ®-RTX) before initiating each treatment course (t=0d) and at 30, 90 and 180 days. We then analyzed the association of serum rituximab levels with changes in DAS28, PCR, ESR, IgG, IgM and IgA levels, B cell frequency, RF and C3 and C4 complement. Results: The peak of rituximab levels was observed at 30 days after initiating each course. Rituximab levels ranged from 13000 to115000 ng/ml at 30d. At 90d levels decreased significantly, but they were still detectable in 80% of patients. Those patients with higher levels in the first course of the treatment presented also higher levels in the second and third courses. No anti-rituximab antibodies were detected during follow-up. To analyze the association of rituximab levels with clinical and immunological parameters, patients were segregated in two groups according to 30d-rituximab levels: group H ( >56000 pg/ml) (52% of patients) and group L (<55000pg/ml) (48% of patients) (Table 1 ). Both groups of patients were comparable before treatment. EULAR response was achieved in 63.4% of Group H patients and 88.9% of group L patients. The decrease of DAS28 was 42% higher in Group L than in group H patients at 90d. Group L patients were also associated with a higher decrease of ESR (p<0.038) at 180d. Depletion of B cells was comparable in the two groups but CD19+ cell recovery was earlier in the peripheral blood of group H patients. Conclusions: Lower levels of rituximab in serum were associated with a better clinical response and later B cell recovery. Circulating levels of rituximab may be conditioned by the relocation of rituximab to the extravascular compartment. In this extravascular compartment, rituximab could thus expand its mechanism of action beyond the peripheral blood. Disclosure of Interest: None Declared